2006
DOI: 10.1017/s0950268806006340
|View full text |Cite
|
Sign up to set email alerts
|

Interpreting serological surveys using mixture models: the seroepidemiology of measles, mumps and rubella in England and Wales at the beginning of the 21st century

Abstract: A mixture modelling technique is applied to age-specific frequency distributions of quantitative results from serological surveys for measles, mumps and rubella using samples collected across the age range in England and Wales in 2000. In accordance with previous studies the analysis suggests that the antibody response to natural infection is stronger than that produced by vaccination, that vaccine-induced antibody levels wane with time and that levels of vaccine-induced antibody response vary for each virus i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
83
1

Year Published

2007
2007
2018
2018

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 73 publications
(87 citation statements)
references
References 15 publications
3
83
1
Order By: Relevance
“…Our finding was consistent with the results of other studies from Italy, Kenya, Poland, England, and Canada (17,22,(27)(28)(29) but in contrast to other study from Turkey reporting lack of association between these two variables (15).…”
Section: Rubellasupporting
confidence: 93%
“…Our finding was consistent with the results of other studies from Italy, Kenya, Poland, England, and Canada (17,22,(27)(28)(29) but in contrast to other study from Turkey reporting lack of association between these two variables (15).…”
Section: Rubellasupporting
confidence: 93%
“…Vyse et al [1] also found a similar age pattern of rubella seronegativity among women in England and Wales. This could be a consequence of the antenatal screening programme, where women who screened negative in a previous pregnancy were vaccinated post partum.…”
Section: Discussionmentioning
confidence: 68%
“…In previous studies where finite mixture models have been used, only age group has been of interest as a predictor of antibody level [1,3,8], and mixture models are therefore often stratified in order to determine the proportion of seronegative samples in each age group. This is important in order to establish whether further vaccination is required due to higher susceptibility in some cohorts.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…1 Outbreaks continue to occur in other global regions, primarily as a result of measles virus importation into areas where vaccine coverage has fallen to a suboptimal level and a susceptible cohort has accumulated. [2][3][4] Most regions have elimination goals and elimination strategies based on the maintenance of high vaccination coverage, for which political commitment is required. A key component of elimination plans is surveillance to monitor impact.…”
Section: Introductionmentioning
confidence: 99%